Developmental exposure to polychlorinated biphenyls (PCBs) in the maternal diet causes host-microbe defects in weanling offspring mice. (October 2019) - Rude, Kavi M.; Pusceddu, Matteo M.; Keogh, Ciara E.; Sladek, Jessica A.; Rabasa, Gonzalo; Miller, Elaine N.; Sethi, Sunjay; Keil, Kimberly P.; Pessah, Isaac N.; Lein, Pamela J.; Gareau, Mélanie G.
Abstract: The gut microbiota is important for maintaining homeostasis of the host. Gut microbes represent the initial site for toxicant processing following dietary exposures to environmental contaminants. The diet is the primary route of exposure to polychlorinated biphenyls (PCBs), which are absorbed via the gut, and subsequently interfere with neurodevelopment and behavior. Developmental exposures to PCBs have been linked to increased risk of neurodevelopmental disorders (NDD), including autism spectrum disorder (ASD), which are also associated with a high prevalence of gastrointestinal (GI) distress and intestinal dysbiosis. We hypothesized that developmental PCB exposure impacts colonization of the gut microbiota, resulting in GI pathophysiology, in a genetically susceptible host. Mouse dams expressing two heritable human mutations (double mutants [DM]) that result in abnormal Ca 2+ dynamics and produce behavioral deficits (gain of function mutation in the ryanodine receptor 1 [T4826I- RYR1 ] and a human CGG repeat expansion [170–200 CGG repeats] in the fragile X mental retardation gene 1 [ FMR1 premutation]). DM and congenic wild type (WT) controls were exposed to PCBs (0–6 mg/kg/d) in the diet starting 2 weeks before gestation and continuing through postnatal day 21 (P21). Intestinal physiology (Ussing chambers), inflammation (qPCR) and gut microbiome (16S sequencing) studies were performed in offspring mice (P28–P30). Developmental exposure to PCBs in the maternal diet caused significant mucosal barrier defects in ileum and colon (increased secretory state and tight junction permeability) of juvenile DM mice. Furthermore, PCB exposure increased the intestinal inflammatory profile ( Il6, Il1β, and Il22 ), and resulted in dysbiosis of the gut microbiota, including altered β-diversity, in juvenile DM mice developmentally exposed to 1 mg/kg/d PCBs when compared to WT controls. Collectively, these findings demonstrate a novel interaction between PCB exposure and the gut microbiota in a genetically susceptible host that provide novel insight into environmental risk factors for neurodevelopmental disorders. Graphical abstract: Image 1 Highlights: Developmental PCBs cause intestinal pathophysiology and dysbiosis in juvenile mice with mutations affecting Ca 2+ signaling. Cytokine expression in both the ileum and colon is altered in a tissue, dose, and genotype specific manner. Intestinal dysbiosis is characterized by altered diversity and colonization of specific taxa.